Stacking of G-quadruplexes: NMR structure of a G-rich oligonucleotide with potential anti-HIV and anticancer activity(†) - Do, Ngoc Quang (Oxford University Press, 2011)
G-rich oligonucleotides T30695 (or T30923), with the sequence of (GGGT)(4), and T40214, with the sequence of (GGGC)(4), have been reported to exhibit anti-HIV and anticancer activity. Here we report on the structure of a dimeric G-quadruplex adopted by a derivative of these sequences in K(+) solution. It comprises two identical propeller-type parallel-stranded G-quadruplex subunits each containing three G-tetrad layers that are stacked via the 5′-5′ interface. We demonstrated control over the stacking of the two monomeric subunits by sequence modifications. Our analysis of possible structures at the stacking interface provides a general principle for stacking of G-quadruplexes, which could have implications for the assembly and recognition of higher-order G-quadruplex structures.